IMPLEMENTASI PENDIDIKAN ANTIKORUPSI UNTUK MENINGKATKAN MORALITAS MAHASISWA PPKN UNIVERSITAS SULTAN AGENG TIRTAYASA - Ade Millatus Sa'adiyyah; Aryanti Dwi Untari; Nibras Shohwatul Islam (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
ABSTRACT The phenomenon of corruption in Indonesia in various aspects of life is not a new thing. Likewise, corrupt behavior has often occurred in everyday life. In fact, ironically, a person sometimes does not know that his actions are corrupt behavior. Corruption is a crime committed either individually or in groups, taking what is not their right with the aim of enriching themselves. Corruption is carried out as a shortcut to enrich oneself without being responsible for the aftermath. The government has taken many ways to make Indonesia free from corruption. However, to realize an Indonesia that is honest and free from acts of corruption is an agenda that requires attention and a very long effort by leaders who are aware of honesty and are free from acts of corruption that are deeply rooted in Indonesian culture. This study aims to: 1) determine the implementation of anti- corruption education in improving the morality of PPKn Untirta students, 2) to find out the learning strategies of anti-corruption education courses in improving the morality of PPKn Untirta students, 3) To find out the forms of morality reflected in PPKn Untirta students. This research is a descriptive research with a qualitative approach. The subjects of this study were the Head of the PPKn Untirta Department, Lecturers of Anti-Corruption Education Courses, and PPKn Students. Data was collected using the methods of observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Test the validity of the data using source triangulation. The results showed that: 1) Implementation of Anti-Corruption Education in Improving the Morale of PPKn Untirta Students, (a) Supporting activities: socialization, seminars, habits. 2) Increasing student morality in implementing anti- corruption values.